STYLISTIC CONVERGENCE IN THE SENSE FIELD OF G. DELEDDA’S NOVEL OF DECADENCE “THE IVY” (ON THE MATERIAL OF DESCRIPTION OF THE CHARACTER OF ANNESA) - Okhrimenko, Valeriia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The article focuses on stylistic convergence in the sense field of G. Deledda’s novel of decadence “The Ivy” on the material of description of the character of Annesa. It has been established that the system of stylistic devices can be defined as stylistic convergence that reflects author's intention to show such topics as crime and punishment, the protagonist's inability to resist passions and the correlation between the inner world, the emotional state of the characters and nature as well as decadence ideas such as social decline of the noble families of Sardinia, disappointment, hopelessness.Our results reveal a correlation between extra-linguistic factors and semantic field of the novel containing quants of information relevant to establish regularities of sense-making. In according to three components of conscience defined by L. Festinger such as affective, cognitive, behavioral we propose to involve in analyses the verbalization of information of perceptive, emotional, epistemic, willing semantics, verbs of movement as well as nouns denoting nature phenomena, household items, shelter.It has been shown that the regularities of information quantization are based on the cognitive principle of salience “background vs figure”. The sense field of G. Deledda’s novel “The Ivy” is based on the referent (the protagonist and her inner properties) being nucleus and referent groups (nature phenomena, household items, shelter) being the pre-nuclear and peripheral zone. The elements of the field are presented according to the cognitive principle of salience “background vs. figure” and correlate with the category of evaluation. The category of evaluation in the analyzed novel is related to color symbolism. Symbols, in particular, those being part of personifications, reflect the author's intention and define regularities of sense-making.Color symbolism acquires special significance if it is associated with symbols that include extended personifications with components that form a gradation. On the one hand, personifications, extended personifications with gradation and similes with color symbolism components containing dark colors are used to denote increasing of the protagonist’s emotional state of affect and the uncontrollability of actions, the inability to resist circumstances. On the other hand, personifications and similes with color symbolism components containing light colours are used to refer to natural phenomena being contrastive background for the protagonist. These stylistic devices can form antithesis at the transphrasal level and extended antithesis at the textonomical level. The semantic components denoting emotions, epistemic state, will and actions of the protagonist being part of personifications are associated with separation, isolation, compression and verbalizes the inability to resist the circumstances, while similes contain semantic components related to destruction, uncontrollability and loss of connection with reality. The main stylistic device in the novel is antithesis expressed at the textonomical level containing components with color symbolism components that acquire an evaluative connotation under the influence of the semantic field. The key metaphors of the novel form an antithesis that reveals the contradiction between aspirations of the protagonist and their realization. The key metonymy of the novel is part of an extended antithesis that describes the confrontation between the external and internal world of the protagonist. The key simile that is significant for revealing the protagonist’s image is associated with color symbolism component symbolizing complete darkness.______________References:• Manakin, V. M. (2004). The contrastive lexicology. Kyiv: Znannya.• Okhrimenko, V. I. (2024). Linguopragmatic features of the meaning field of descriptive texts (on the material of description of the character of the Unknown in the novel by A. Manzoni The Betrothed). Problems of Semantics, Pragmatics and Cognitive Linguistics, 45, 79–93.• Okhrimenko, V. I. (2023). Linguopragmatic features of the functioning of affixal derivatives in the meaning field of L. Capuana’s novel The Marquis of Roccaverdine. Problems of Semantics, Pragmatics and Cognitive Linguistics, 44, 103–115.• Okhrimenko, V. I. (2024). Linguopragmatic features of the functioning of stylistic devices in the meaning field of G. Deledda’s decadent novel The Ivy. Problems of Semantics, Pragmatics and Cognitive Linguistics, 46, 70–87.• Okhrimenko, V. I. (2012). Ontology and gnoseology of the category of modality in Italian (Doctoral dissertation). Kyiv University.• Syz’ko, G. (n.d.). Worldview and aesthetic shifts in art and literature of the mid-second half of the 19th century. https://www.slideshare.net/slideshow/xix-55919192/55919192 (accessed October 15, 2024)• Zubrytska, M. (Ed.). (1996). Word. Sign. Discourse: An anthology of world literary and critical thought of the 20th century. Lviv: Litopys.• Grazia Deledda, tra Verismo e Decadentismo. (n.d.). StudiaRapido.it. https://www.studiarapido.it/grazia-deledda-verismo-e-decadentismo/ (accessed February 20, 2025)• Festinger, L. (1962). A theory of cognitive dissonance. Stanford, CA: Stanford University Press.• Fillmore, C. (1976). Frame semantics and the nature of language. In Annals of the New York Academy of Sciences: Conference on the Origin and Development of Language and Speech, 280, 20–32.• Riffaterre, M. (1959). Criteria for style analysis. Word, 15(1), 154–174.• Deledda, G. (1950). L’edera. Milano: Mondadori.
Keywords: stylistic devices, stylistic convergence, linguopragmatics, sense field, referent groups, decadence, Italian language